2014
DOI: 10.3109/00016489.2013.879740
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and oxaliplatin are toxic to cochlear outer hair cells and both target thioredoxin reductase in organ of Corti cultures

Abstract: ConclusionInhibition of thioredoxin reductase (TrxR) may be a contributing factor in cisplatin-induced ototoxicity. Direct exposure of organ of Corti to cisplatin and oxaliplatin gives equal loss of hair cells.ObjectivesPlatinum-containing drugs are known to target the anti-oxidant selenoprotein TrxR in cancer cells. Two such anti-cancer, platinum-containing drugs, cisplatin and oxaliplatin, have different side effects. Only cisplatin induces hearing loss, i.e. has an ototoxic side effect that is not seen afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
0
15
2
2
Order By: Relevance
“…The uptake of cisplatin in the cochlea is obligatory for the ototoxic side effects. Our previous findings based on pharmacokinetic studies suggested that the ototoxic effect of cisplatin is related to the drug concentration in the perilymphatic compartments . The findings in this study give no support that OCT2 is primarily involved in the uptake of cisplatin from the systemic circulation but does not exclude an OCT2‐mediated transport from deeper compartments of the cochlea to the target cells for cisplatin.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The uptake of cisplatin in the cochlea is obligatory for the ototoxic side effects. Our previous findings based on pharmacokinetic studies suggested that the ototoxic effect of cisplatin is related to the drug concentration in the perilymphatic compartments . The findings in this study give no support that OCT2 is primarily involved in the uptake of cisplatin from the systemic circulation but does not exclude an OCT2‐mediated transport from deeper compartments of the cochlea to the target cells for cisplatin.…”
Section: Discussioncontrasting
confidence: 87%
“…Our previous findings based on pharmacokinetic studies suggested that the ototoxic effect of cisplatin is related to the drug concentration in the perilymphatic compartments. 32,37 The findings in this study give no support that OCT2 is primarily involved in the uptake of cisplatin from the systemic circulation but does not exclude an OCT2mediated transport from deeper compartments of the cochlea to the target cells for cisplatin. The complex processes that take place in cisplatin-induced ototoxicity probably involve several series of events, of which influx of the drug to target cells is the crucial first step.…”
Section: Discussioncontrasting
confidence: 71%
“…Common antitumor drugs such as oxaliplatin are reliable for the clinical treatment of gastric cancer. However, long-term use of oxaliplatin can result in nephrotoxicity [20], ototoxicity [21], neurotoxicity [22], and myelosuppression [23]. Moreover, the resistance of tumor cells to oxaliplatin reduces the efficacy of the drug and is a major cause of chemotherapy failure [24].…”
Section: Discussionmentioning
confidence: 99%
“…18 Thioredoxin is kept in a reduced state by thioredoxin reductase (TXNRD1, OMIM 601112) and its related isoenzymes. Dammeyer et al 19 found that TXNRD1 was strongly expressed in rat cochlea and that exposure to cisplatin and oxaliplatin significantly reduced TXNRD1 activity. Tadros et al 20 demonstrated that TXNRD1 expression was downregulated in mice cochlea with age-related hearing loss.…”
Section: Methodsmentioning
confidence: 99%